The Moderating Role of Grit in the Relationship Between Perfectionism and Depression Among Chinese College Students - Zhang, Jing; Liu, Luming; Wang, Wenchao (Frontiers in Psychology, 2021)
Background: As a personality trait, perfectionism has shown a close association with psychological disorders, such as depression. The protective effect of grit on depression has been confirmed by a series of recent studies. Therefore, it is necessary to investigate the buffering role of grit in the above relationship and the possible underlying mechanism. Objective: Based on the multidimensional theory of perfectionism, we differentiated two dimensions of perfectionism as positive and negative and further examined the relationships between these two dimensions of perfectionism and depression. We also aimed to examine the possible moderating effect of grit on the above two relationships. Methods: Us a questionnaire survey approach, a total of 2,602 college students (1,608 females and 994 males) were assessed using the Frost Multidimensional Perfectionism Scale (FMPS), the Short Grit Scale, and the Center for Epidemiological Studies-Depression Scale (CES-D). Hierarchical regression analysis was used to investigate the direct effect of two dimensions of perfectionism on depression as well as the moderating role of grit in these associations. Results: After controlling for gender, age, family income, and academic performance, both positive and negative perfectionism had positive predictive effects on depression, and grit negatively moderated these two relationships. Specifically, grit completely counteracted the effect of positive perfectionism on depression yet partly counteracted the effect of negative perfectionism on depression. Conclusions: Grit prevents the depressive symptoms raised by positive and negative perfectionism.